2008
DOI: 10.1093/ndt/gfm828
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in type-2 diabetics with early diabetic nephropathy is associated with low circulating adiponectin

Abstract: The present study suggests that the presence of proteinuria, regardless of the degree of renal function impairment, is an important predictor of endothelial dysfunction in early diabetic nephropathy and that it is associated with altered circulating levels of NAMPT/visfatin and adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 31 publications
6
66
2
8
Order By: Relevance
“…In the present study, we showed that ezetimibe treatment improved hyperlipidemia, albuminuria, and glomerular hypertrophy in db/db mice, implying a beneficial role of ezetimibe in early diabetic nephropa- Several human and animal studies have reported that hypoadiponectinemia is associated with renal dysfunction [21][22][23] . In the present study, we observed the improvement of hypoadiponectinemia by ezetimibe treatment in db/db mice; however, we did not find a correlation between the effect of ezetimibe on albuminuria and on adiponectin in db/db mice (data not shown), suggesting that improvement of hypoadiponectinemia may not be responsible for the renoprotective effect of ezetimibe in db/db mice.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, we showed that ezetimibe treatment improved hyperlipidemia, albuminuria, and glomerular hypertrophy in db/db mice, implying a beneficial role of ezetimibe in early diabetic nephropa- Several human and animal studies have reported that hypoadiponectinemia is associated with renal dysfunction [21][22][23] . In the present study, we observed the improvement of hypoadiponectinemia by ezetimibe treatment in db/db mice; however, we did not find a correlation between the effect of ezetimibe on albuminuria and on adiponectin in db/db mice (data not shown), suggesting that improvement of hypoadiponectinemia may not be responsible for the renoprotective effect of ezetimibe in db/db mice.…”
Section: Discussionsupporting
confidence: 57%
“…These results agreed with the results of Julie et al [21] and these of Ran J.et al [22] who have concluded a higher serum adiponectin concentration which was associated with reduced renal function in type 2 diabetics as the kidney was involved in the degradation and/or elimination of adiponectin, although it was unlikely to be the sole mechanism. Yilmaz et al reported that vascular endothelial dysfunction existed in untreated early diabetic nephropathy patients with severe proteinuria and decreased plasma adiponectin concentration, which was contradictory to our results.…”
Section: Methodssupporting
confidence: 93%
“…Elevated glucose levels could promote inflammation by increased oxidative stress. [22,23,24] Another possibility is that inflammatory response is a result of vascular complications following diabetes. The acute-phase response refers to a non specific and complex reaction of the individual that occurs shortly after a tissue injury.…”
Section: Methodsmentioning
confidence: 99%
“…However, Xiang et al (19) did not find any relation between plasma osteoprotegerin and BMI, total cholesterol, triglycerides, LDLcholesterol, or HDL-cholesterol. In contrast, OPG was positively correlated with insulin resistance in an obese population (30) and in men with T2DM. (31) Regarding ghrelin in this study, it was significantly lower in diabetic patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 76%